ANALISIS USABILITY PADA APLIKASI INDOFARM UNTUK MENGUKUR TINGKAT KEPUASAN PELANGGAN MENGGUNAKAN CUSTOMER SATISFACTION INDEX DAN USER EXPERIENCE QUESTIONNAIRE - Pramanda, Riska; Ilhamsyah; Mutiah, Nurul (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
The rapid growth of digitalization has driven the expansion of E-Commerce, including the Indofarm application in Pontianak, which provides grocery delivery services. However, users have reported issues related to system performance and service quality. This study evaluates customer satisfaction using the Customer Satisfaction Index (CSI) and User Experience Questionnaire (UEQ) with 26 measurement indicators. The results show a CSI score of 52.70%, indicating a "moderately satisfied" category. Importance Performance Analysis (IPA) identifies seven attributes—speed, security, motivation, expectations, efficiency, organization, and attractiveness—as critical areas for improvement. Additionally, one attribute, "Pleasant," is rated highly but is of lower priority. The findings suggest that Indofarm should focus on enhancing key service aspects while reallocating resources from less critical attributes to improve overall customer satisfaction.